Under the spotlight: The organic–inorganic hybrid halide perovskite for optoelectronic applications. Issue 3 (June 2015) - Chen, Qi; De Marco, Nicholas; Yang, Yang (Michael); Song, Tze-Bin; Chen, Chun-Chao; Zhao, Hongxiang; Hong, Ziruo; Zhou, Huanping; Yang, Yang
Graphical abstract: Highlights: A review of hybrid perovskites in high performance optoelectronic applications. Material properties governing device working mechanisms have been discussed. PV application covers film formation, interface engineering, tandem devices and etc. Other optoelectronic applications such as photodetectors, LEDs, lasers, and transistors. Summary: The dawn of a new era in optoelectronic technologies has emerged with the recent development of the organic–inorganic hybrid halide perovskite. Its exceptional attributes, including high carrier mobility, an adjustable spectral absorption range, long diffusion lengths, and the simplicity and affordability of fabrication render it one of the most exceptional and market-competitive optoelectronic materials for applications in photovoltaics, light emitting diodes (LED), photodetectors, lasers, and more. Moreover, its versatility in device architecture and ability to achieve relatively high performance devices via various processing techniques makes perovskites a highly promising material for various practical applications. Here, we review the organic–inorganic hybrid halide perovskite and delve into its recent progress and relevant applications.